Neural activity patterns in the chemosensory network encoding vomeronasal and olfactory information in mice - Pardo-Bellver, Cecília; Vila-Martin, Manuel E.; Martínez-Bellver, Sergio; Villafranca-Faus, María; Teruel-Sanchis, Anna; Savarelli-Balsamo, Camila A.; Drabik, Sylwia M.; Martínez-Ricós, Joana; Cervera-Ferri, Ana; Martínez-García, Fernando; Lanuza, Enrique; Teruel-Martí, Vicent (Frontiers in Neuroanatomy, 2022)
Rodents detect chemical information mainly through the olfactory and vomeronasal systems, which play complementary roles to orchestrate appropriate behavioral responses. To characterize the integration of chemosensory information, we have performed electrophysiological and c-Fos studies of the bulbo–amygdalar network in freely behaving female mice exploring neutral or conspecific stimuli. We hypothesize that processing conspecifics stimuli requires both chemosensory systems, and thus our results will show shared patterns of activity in olfactory and vomeronasal structures. Were the hypothesis not true, the activity of the vomeronasal structures would be independent of that of the main olfactory system. In the c-Fos analysis, we assessed the activation elicited by neutral olfactory or male stimuli in a broader network. Male urine induced a significantly higher activity in the vomeronasal system compared to that induced by a neutral odorant. Concerning the olfactory system, only the cortex–amygdala transition area showed significant activation. No differential c-Fos expression was found in the reward system and the basolateral amygdala. These functional patterns in the chemosensory circuitry reveal a strong top-down control of the amygdala over both olfactory bulbs, suggesting an active role of the amygdala in the integration of chemosensory information directing the activity of the bulbs during environmental exploration.